Institute of corporate responsibility in the system of valuation for stakeholders - Ківалов, Сергій Васильович; Ківалов, С. В.; Кивалов, Сергей Васильевич; Kivalov, Serhii V.; Кібік, Ольга Миколаївна; Кібік, О. М.; Кибик, Ольга Николевна; Kibik, Olha M.; Kivalov, Sergey; Kibik, Olha (EDP Sciences, 2019)
The principles and terms for providing corporate responsibility of economic agents of different levels are determined. Formation features of modern system for providing corporate responsibility of economic agents are examined on the example of agents operating in the field of port activity. The purpose of the article is to study concepts of development of the mechanism for corporate responsibility in order to optimize the system of stakeholders’ interaction in the process of creating values. The method of system analysis was applied in studying concepts and preconditions for the functioning of corporate responsibility management systems. The systemic structural method helped in studying basic measures to increase the corporate responsibility level of enterprises of port activity. The goal of creating a system of corporate responsibility should be associated with the achievement of the maximum possible effect of functioning of the economic agent. Needs and contributions of stakeholders should be interlinked in order to increase corporate responsibility. The main stakeholders in the field of port activity and criteria for satisfying their needs, contribution and opportunities in the field of corporate responsibility have been identified. The proposed system of criteria for the effectiveness will improve the mechanism of corporate responsibility management.
Kivalov S. Institute of corporate responsibility in the system of valuation for stakeholders / S. Kivalov, O. Kibik. - SHS Web of Conferences “International Transport Infrastructure, Industrial Centers and Corporate Logistics”. - Vol. 67. - EDP Sciences, 2019. - 6 p.
Keywords: corporate responsibility; providing of corporate responsibility; stakeholders; economic agent; port activity; корпоративна відповідальність; забезпечення корпоративної відповідальності; стейкхолдери; економічний агент; портова діяльність; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::SOCIAL SCIENCES::Business and economics